2014
DOI: 10.1007/s00213-014-3725-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in anhedonic and accumbal dopamine responses to chronic social stress and their link to cocaine self-administration in female rats

Abstract: Rationale Women are twice as likely as men to develop major depressive disorder. Exposure to chronic stress can induce depression in some vulnerable individuals, while others are resistant to depressive-like symptoms after equivalent levels of chronic stress. Objectives In female rats, individual differences in saccharin intake during chronic social defeat stress may predict subsequent cocaine self-administration, and may be attributed to alterations in mesolimbic dopamine activity. Methods Female rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 46 publications
4
38
0
Order By: Relevance
“…Additionally, our results showed that adolescent MSEW group of mice reduced the consumption of saccharin, suggesting that early life neglect induced responses related to anhedonia, a core symptom of depressive states that could be observed in rodents after the exposure to a chronic stress (D'Aquila et al, 1997;Harkin et al, 2002;Strekalova et al, 2004), like the MSEW procedure. Our results agree well with previous data showing a reduced in the saccharin consumption in two accepted model to induce a depressive-like state in rodents as chronic mild stress (Harkin et al, 2002;Pijlman et al, 2003;Schweizer et al, 2009), and social defeat (Furay et al, 2011;Shimamoto et al, 2015).…”
Section: Discussionsupporting
confidence: 95%
“…Additionally, our results showed that adolescent MSEW group of mice reduced the consumption of saccharin, suggesting that early life neglect induced responses related to anhedonia, a core symptom of depressive states that could be observed in rodents after the exposure to a chronic stress (D'Aquila et al, 1997;Harkin et al, 2002;Strekalova et al, 2004), like the MSEW procedure. Our results agree well with previous data showing a reduced in the saccharin consumption in two accepted model to induce a depressive-like state in rodents as chronic mild stress (Harkin et al, 2002;Pijlman et al, 2003;Schweizer et al, 2009), and social defeat (Furay et al, 2011;Shimamoto et al, 2015).…”
Section: Discussionsupporting
confidence: 95%
“…Similarly, we have recently reported individual differences in anhedonic-like responses following chronic social defeat stress in female rats (9). Female rats were characterized as either ‘stress-vulnerable’ or ‘stress-resistant’ based upon saccharin preference during chronic social defeat, and only one subgroup showed increased cocaine self-administration during a 24 h “binge”, as well as suppressed cocaine-induced extracellular dopamine efflux in the nucleus accumbens shell.…”
Section: Individual Differences In Sud Comorbiditysupporting
confidence: 63%
“…Social defeat in California mice has been optimized so that on average males and females are exposed to the same number of aggressive interactions across three episodes of defeat (Trainor et al , 2013). Lactating rat dams are used to induce defeat in female rats (Holly et al , 2012; Shimamoto et al , 2015). Although aggression levels of males and lactating dams are typically not compared in the same study, long lasting behavioral changes are induced (Holly et al , 2012; Shimamoto et al , 2015).…”
Section: What Is Social Defeat Stress?mentioning
confidence: 99%
“…Lactating rat dams are used to induce defeat in female rats (Holly et al , 2012; Shimamoto et al , 2015). Although aggression levels of males and lactating dams are typically not compared in the same study, long lasting behavioral changes are induced (Holly et al , 2012; Shimamoto et al , 2015). Interestingly, female Syrian hamsters are more aggressive than males (Payne & Swanson, 1970), which has facilitated studies of defeat stress in female hamsters.…”
Section: What Is Social Defeat Stress?mentioning
confidence: 99%